SISTEM INFORMASI PEMBELIAN DAN PENJUALAN PAKAIAN PADA GALOENK DISTRO PEMATANGSIANTAR - Victor Marudut Mulia Siregar (Universitas Asahan, 2017)
Abstrack - Galoenk Distro is a store engaged in the sale of clothing in the city of Pematangsiantar. Processing data on the sale of goods on Galoenk distributions is still done by recording transactions manually on sales invoices and cash books, so that the control of clothing stock and the report making process is less efficient. The design of information systems for buying and selling clothing is done to overcome the inefficient data processing of purchases and sales at the store. This information system provides convenience in processing sales and purchase transactions and minimizes errors that occur in recording sales and sales data per period, so as to produce more precise and accurate sales and purchase reports. Keywords - Information Systems, Sales, Purchases, Efficient, Accurate, Distro